A review of the literature of Listeria monocytogenes in Africa highlights breast milk as an overlooked human source - Sarr, Marièma; Alou, Maryam Tidjani; Padane, Abdou; Diouf, Fatou Samba; Beye, Mamadou; Sokhna, Cheikh; Fenollar, Florence; Mboup, Souleymane; Raoult, Didier; Million, Matthieu (Frontiers in Microbiology, 2023)
According to the latest WHO estimates (2015) of the global burden of foodborne diseases, Listeria monocytogenes is responsible for one of the most serious foodborne infections and commonly results in severe clinical outcomes. The 2013 French MONALISA prospective cohort identified that women born in Africa has a 3-fold increase in the risk of maternal neonatal listeriosis. One of the largest L. monocytogenes outbreaks occurred in South Africa in 2017-2018 with over 1,000 cases. Moreover, recent findings identified L. monocytogenes in human breast milk in Mali and Senegal with its relative abundance positively correlated with severe acute malnutrition. These observations suggest that the carriage of L. monocytogenes in Africa should be further explored, starting with the existing literature. For that purpose, we searched the peer-reviewed and grey literature published dating back to 1926 to date using six databases. Ultimately, 225 articles were included in this review. We highlighted that L. monocytogenes is detected in various sample types including environmental samples, food samples as well as animal and human samples. These studies were mostly conducted in five east African countries, four west African countries, four north African countries, and two Southern African countries. Moreover, only  0.2% of the Listeria monocytogenes genomes available on NCBI were obtained from African samples, contracted with its detection. The pangenome resulting from the African Listeria monocytogenes samples revealed three clusters including two from South-African strains as well as one consisting of the strains isolated from breast milk in Mali and Senegal and, a vaginal post-miscarriage sample. This suggests there was a clonal complex circulating in Mali and Senegal. As this clone has not been associated to infections, further studies should be conducted to confirm its circulation in the region and explore its association with foodborne infections. Moreover, it is apparent that more resources should be allocated to the detection of L. monocytogenes as only 15/54 countries have reported its detection in the literature. It seems paramount to map the presence and carriage of L. monocytogenes in all African countries to prevent listeriosis outbreaks and the related miscarriages and confirm its association with severe acute malnutrition.